Süryani Hristiyan ve Sünni Müslüman Çocuklarda Tanrı Tasavvuru - Bektaş, Aylin; Emre, Yusuf (Siirt University, 2025)
Bu çalışmanın amacı ikinci çocukluk döneminde bulunan çocukların soyut bir kavram olan Tanrı’yı nasıl tasavvur ettiklerini anlamaktır. Aynı coğrafyada ikamet eden farklı dine mensup çocukların Tanrı hakkında ne düşündükleri, buna bağlı olarak tasavvur sürecinin nasıl şekillendiği, araştırmanın problemini oluşturmaktadır. Bu amaçla Şırnak ilinde ikamet eden yaşları 6-11 arasında değişen 12 Süryani Hristiyan ve 12 Sünni Müslüman olmak üzere toplam 24 çocuk ile mülakat yapılmıştır. Çalışmada nitel araştırma yöntemlerinden fenomenoloji deseni kullanılmıştır. Mülakat verileri betimsel analiz aracılığı ile çözümlenmiş ve yorumlanmıştır. Araştırma sonucuna göre her iki dine mensup çocukların da insanbiçimci Tanrı anlayışına sahip olduğu tespit edilmiştir. Çocukların tasavvurlarında inandıkları dinin, Tanrı’ya yüklediği niteliklerin yansımaları görülmüştür. Araştırma verilerinden hareketle oluşturulan kod ve kategoriler “İnsan biçimli Tanrı”, “Tanrı’nın nitelikleri” ve “Tanrı’nın konumu” olmak üzere üç tema altında toplanmıştır. Tanrı hakkında konuşurken çocukların çoğunlukla benzer ifadelerde bulunmaları içinde bulunduğu gelişim özelliklerinin etkisine işaret etmektedir. Farklı yorum getirdikleri ifadelerde ise sosyal çevrenin ve dini öğretilerin etkisi görünür hale gelmiştir.

The aim of this study is to understand how children in the late childhood period conceptualize God, an abstract concept. The research problem is shaped around what children of different religions, living in the same geographical region, think about God and how their conceptualization process is formed accordingly. For this purpose, interviews were conducted with a total of 24 children aged between 6 and 11, including 12 Syriac Christian (6 girls, 6 boys) and 12 Sunni Muslim children (6 girls, 6 boys) residing in the province of Şırnak. This study employed a phenomenological design, a qualitative research approach, within the framework of criterion sampling. The interview data were analyzed and interpreted through descriptive analysis. According to the results of the study, it was determined that children of both religions possess an anthropomorphic understanding of God. The reflections of the characteristics attributed to God by the religion they believe in were observed in the children’s conceptualizations. The codes and categories derived from the research data were grouped under three main themes: “Anthropomorphic God”, “Attributes of God”, and “Position of God”. The fact that children mostly used similar expressions while talking about God indicates the influence of their developmental characteristics. On the other hand, the influence of social environment and religious teachings became evident in expressions where they provided different interpretations.
The Concept of God in Syriac Christian and Sunni Muslim Children
Keywords: Psychology of Religion; Din Psikolojisi